NLRC4 inflammasome is an important regulator of interleukin-18 levels in patients with acute coronary syndromes - Johansson, Åsa; Katus, Hugo (Circulation. Cardiovascular genetics, 2015)
Background—Interleukin 18 (IL-18) promotes atherosclerotic plaque formation and is increased in patients with acute coronary syndromes. However the relative contribution of genetic variants to the IL-18 levels has not been fully determined. Methods and Results—Baseline plasma IL-18 levels were measured in 16 633 patients with acute coronary syndrome, of whom 9340 had genetic data that passed genotype quality control. A 2-stage genome-wide association study was performed, followed by combined analyses using >10 million genotyped or imputed genetic markers. Single nucleotide polymorphisms at 3 loci (IL18, NLRC4, and MROH6) were identified (P<3.15×10−8) in the discovery cohort (n=3777) and replicated in the remaining patients (n=5563). In the pooled data (discovery+replication cohort), 7 independent associations, in 5 chromosomal regions, were associated with IL-18 levels (minimum P=6.99×10-72). Six single nucleotide polymorphisms are located in predicted promoter regions of which one disrupts a transcription factor binding site. One single nucleotide polymorphism in NLRC4 is a rare missense variant, predicted to be deleterious to the protein. Altogether, the identified genetic variants explained 8% of the total variation in IL-18 levels in the cohort. Conclusions—Our results show that genetic variants play an important role in determining IL-18 levels in patients with acute coronary syndrome and we have identified genetic variants located in the IL-18 gene (IL18) or close to genes that are involved in procaspase-1 activation (NLRC4 and CARD16, CARD17, and CARD18). These associations also highlight the importance of the NLRC4 inflammasome for IL-18 production in acute coronary syndrome patients.